Madagascar Economic Update, December 2020 : Setting a Course for Recovery - World Bank (World Bank, Washington, DC, 2020)
Prior to the pandemic, Madagascar was on sustained recovery path and achieved progress in poverty reduction. The economic revival in the period leading up to the COVID-19 (coronavirus) crisis was supported by political and economic stability, renewed investor confidence, rising integration in key export markets, growing flows of concessional financing and structural reforms. Activity continued to gain strength up until 2019, as public and private sector investments accelerated, while moderate inflation helped support real income and consumer spending. At the same time, budget and current account deficits remained moderate and the currency stabilized in real effective terms. In this context, growth reached 4.4 percent in 2019, its fastest pace in over a decade, with export-oriented sectors such as textiles, mining, and tourism performing particularly well in the run-up to the crisis. Tourism revenues were bolstered by a 19 percent increase in visitor arrivals, reaching a decade high of 375.000. In the primary sector, favorable weather conditions have contributed to a bumper rice harvest and significant gains in agricultural production more generally. The COVID-19 pandemic triggered a sudden and deep recession, reversing nearly a decade of prior income per capita gains. The combined impact of global trade disruptions and domestic containment measures is estimated to have resulted in a GDP contraction of -4.2 percent in 2020, similar to that observed during the devastating 2009 constitutional crisis. Considering a pre-crisis projection of 5.2 percent in 2020, this means that income per capita would be 9.4 percent lower than expected at the start of the year, erasing all gains achieved since the return to constitutional order in 2013. On the demand side, a sharp drop in exports was the key driver of the decline in activity, while public consumption and investment played a buffeting role. The COVID-19 crisis was an external shock of unprecedented magnitude. The contraction in global activity in 2020, currently estimated at -4.4 percent, would be by far the most severe and broad-based on records, with output shrinking in more than 90 percent of countries around the world, against 83 percent during the great depression in 1930, and 60 percent during the great recession 2009. In the Euro Area—Madagascar’s largest export destination—output is estimated to contract by 7.4 percent. As the global toll of the pandemic continues to increase, millions of people are suffering from diminished prospects and disrupted livelihoods. In the developing world, falling income per capita in the vast majority of countries will interrupt poverty reduction trends and could tip over more than 100 million people into extreme poverty.